Savings, entrepreneurial trait and self-employment: evidence from selected Ghanaian Universities - James A. Peprah; Clifford Afoakwah; Isaac Koomson (Journal of Global Entrepreneurship Research, 2015)
Youth unemployment is a major setback to sustainable growth. In recent times, Ghana has experienced a downward trend in youth employment in spite of several attempts made by the government to control the unemployment situation. This paper explores savings behaviour, entrepreneurial trait and the decision to be self-employed among students from selected public and private universities in Ghana. Employing the bivariate analysis and probit model on a sample of 1046 students shows that savings behaviour among the youth varies according to their programmes of study, type of institution (public and private) and family background of the students. Savings and entrepreneurial trait increase the probability of self-employment decision among university students. Policies that can address graduate unemployment should focus on helping students to save while in school. Also, incorporating entrepreneurial training into the academic programmes of these institutions has the tendency of improving the entrepreneurial traits of students and thereby, decide to be self-employed. Policy intervention needs to be designed strategically to target students into self-employment as a way of curbing youth unemployment in Ghana in order to contribute to national development.
Keywords: 650; Entrepreneurial trait; Ghana; Youth unemployment; Savings; Self-employment